Creativity in architecture: expressing conceptual foundations in sketch model experimentation - Márcio Moraes Valença (Cogent Arts & Humanities)
The objective in this article is to discuss creativity in architecture, first presenting a general conceptual foundation, and then presenting four experiments with physical, sketch (concept) models to highlight their strength both as a means of expression and as a cognitive mechanism in the process of architectural design thinking. The experiments are followed by a discussion of the resulting models. The experiments were undertaken with undergraduate, graduate and postgraduate (MPhil and PhD) students of architecture as well as professional architects in four different academic contexts. A methodological mix of theoretical and practical exercises was used. The theoretical background provided during the experiments were targeted at the development of the practical exercises. Notwithstanding, although the exercises were done within the university, they related both to the development of a supporting pedagogical tool as well as a tool to facilitate professional practice. Results show that even untrained students – people who never had any contact with architectural modelling – had no difficulties in engaging with the exercise, building concept models that had a clear architectural nature, whether more abstract or more representative of concrete buildings.